2018
DOI: 10.1111/ppl.12743
|View full text |Cite
|
Sign up to set email alerts
|

Differences in physiological and biochemical characteristics in response to single and combined drought and salinity stresses between wheat genotypes differing in salt tolerance

Abstract: The combined drought and salinity stresses pose a serious challenge for crop production, but the physiological mechanisms behind the stresses responses in wheat remains poorly understood. Greenhouse pot experiment was performed to study differences in genotype response to the single and combined (D + S) stresses of drought (4% soil moisture, D) and salinity (100 mM NaCl, S) using two wheat genotypes: Jimai22 (salt tolerant) and Yangmai20 (salt-sensitive). Results showed that salinity, drought and/or D + S seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(39 citation statements)
references
References 43 publications
7
25
0
Order By: Relevance
“…Root growth rate may be severely affected by saline soils and reduction may even be recorded in salt-tolerant plants. In agreement with previously published studies on the effects of salinity on root elongation (Cirillo et al, 2019; Dugasa et al, 2019), salinity treatments were found to cause stunted root growth. The growth-promoting effect under salinity stress could be due to an increase in the osmotic potential of the cells in the elongation zone coupled with enhanced cell division.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Root growth rate may be severely affected by saline soils and reduction may even be recorded in salt-tolerant plants. In agreement with previously published studies on the effects of salinity on root elongation (Cirillo et al, 2019; Dugasa et al, 2019), salinity treatments were found to cause stunted root growth. The growth-promoting effect under salinity stress could be due to an increase in the osmotic potential of the cells in the elongation zone coupled with enhanced cell division.…”
Section: Discussionsupporting
confidence: 92%
“…The resistance and response of plants to a salt stress varies according to its species or varieties or genotypes or variety and environment which could be attributed to the biological dissimilarities between the species or varieties or genotypes, plant growth, and composition and concentration of the salt stress conditions (Bertazzini et al, 2018; Filichkin et al, 2018; Shabala et al, 2013). Many reports have shown that short term salinity stress significantly affects the germination rate, seedling and root growth as well as ion composition, levels of relative water content, photosynthetic pigments, proline content, level of membrane lipid peroxidation as well as the amounts of reducing sugars and total protein (Dugasa et al, 2019; Sarabi et al, 2017; Kumar and Khare, 2016). These physiological and biochemical indices multivariate cluster analysis been used for classification of salt-sensitive and salt-tolerant varieties so that they can further be used in plant breeding programmes.…”
Section: Introductionmentioning
confidence: 99%
“…In a similar way, drought stress besides causing water deficit and cell turgor loss, causes overproduction of highly reactive oxygen species (ROS) such as superoxide (O 2 − ), and hydrogen peroxide (H 2 O 2 ). This causes reduced growth, mineral shortages and photosynthetic imbalance (Dugasa et al ). The physiological and biochemical plants responses to the combination of drought and salinity are remarkable and cannot be directly assessed from the plants responses to single stress (Mittler ).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, salt‐tolerant rootstocks screening supplies an alternate origin to improve the breeding programs and applies them in order to try comprehend the pathways involved in the mechanism of salt tolerance (Akbari et al ). Besides environmental interactions mainly affecting tolerance to drought, various species, subspecies and crop cultivars under the same conditions show alternations in drought tolerance (Dugasa et al ). Thus, genetic diversity is a major fundamental factor in research associated with drought.…”
Section: Introductionmentioning
confidence: 99%
“…Once the plant is under salt stress, multiple signal transduction pathways are activated to cope with salt stress [ 2 , 4 , 5 , 6 ]. In recent years, although extensive studies among ion uptake and transport, osmotic regulation, hormone metabolism, antioxidant metabolism, and stress signaling have made significant progress [ 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 ], the molecular mechanisms involved in salt tolerance remain to be elucidated. In addition, next-generation high-throughput sequencing based RNA-seq analysis has been widely used to uncover expression patterns under abiotic stress, and it provides a comprehensive means of identifying and studying the differential expression genes [ 12 , 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%